Impact of the Low-Price Medicine Policy on Medicine Supply in China: An Interrupted Time-Series Analysis - Zhao, Mingyue; Gillani, Ali Hassan; Ji, Duan; Feng, Zhitong; Fang, Yu; Yang, Caijun (Frontiers in Pharmacology, 2021)
Abstract Objectives: The primary objective of the study was to assess the impact of the Low-Price Medicine Policy (LPMP) on the supply of low-price medicines (LPMs) in China. The secondary objective of the study was to describe the supply situation of LPMs from 2005 to 2018. Methods: The LPMP was launched in the third quarter of 2014 (2014Q3). An interrupted time series analysis was used to evaluate the impact of LPMP on the supply of LPMs in China. Ordinary least squares and Poisson regression models were utilized to estimate the effect of LPMP on LPMs’ supply growth rate and the number of supplied LPMs. All the LPMs were divided into two subgroups: intermittent supply and continuous supply. The trend and level changes of the quarterly average growth rate and number of quarterly supplies for different LPM groups were analyzed from 2005 to 2018. Findings: For the quarterly average growth rate, before the intervention, a significant increasing trend was observed in the total group and the continuous supply subgroup; after the introduction of LPMP, the increasing trend was ceased and a significant decrease in the trend and level was noted for both the total group (trend coefficient: β3=-0.0132, P<0.01; level coefficient: β2=-0.1510, P<0.05) and the continuous supply subgroup (trend coefficient: β3=-0.0133, P<0.01; level coefficient: β2=-0.1520, P<0.05); whereas it had no significant effect for intermittent supply subgroup. For the number of quarterly supplies, after the intervention of LPMP, decline of the supply number was observed (trend coefficient: β3=-0.0027, P<0.001; level coefficient: β2=-0.0584, P<0.001); whereas the LPMP was associated with an upward trend and level (trend coefficient: β3=0.0715, P<0.001; level coefficient: β2=0.174) for the intermittent supply subgroup. Conclusion: For most of the LPMs, LPMP did not meet the goal of stimulating LPM production. However, for severely shortage medicines (the intermittent supply subgroup), the effect of LPMP was positive. Comprehensive policies rather than just deregulating medicine price should be introduced to alleviate the situation of medicine shortage in China.